Analysis on the characteristics of wind speed and wind energy resources from 1961 to 2020 and the impact of urban underlying surface change on them in Shenyang. (September 2022) - Wang, Yangfeng; Lu, Zhongyan; Ma, Yanjun; Li, Xiaolan; Ren, Wanhui; Zou, Xudong
Abstract: The long-term variation trend of wind speed, monthly variation characteristics and grade frequency of wind energy density and the impact of underlying surface on wind speed in the process of urbanization are analyzed by using the observational wind speed data from 1971 to 2020 in Shenyang and WRF models simulation. The results show that the wind speed has shown a linear decreasing trend year by year at the rate of 0.018 m s −1 every year since 1961 in Shenyang and The decreasing trend of wind speed has slowed down significantly since 2010. The wind speed and wind energy density show obvious monthly variation characteristics with three peaks in Shenyang. The peak value appears in April, with the monthly average wind speed of 3.76 m s −1 and the monthly average wind energy density of 58.3 W m −2 . The southwest wind is the dominant wind direction in Shenyang all year round, and the occurrence frequencies of southwest wind and south–south​ west wind are 12% and 10% respectively, which account for about one quarter of the annual wind direction frequency. Due to the different types of underlying surfaces in numerical simulation, the intensity of 10 m wind speed in most areas of Liaoning Province is slightly weakened, and the average wind speed is reduced by 0.15 m s −1 in Shenyang. So the development of urbanization is one of the reasons for the decrease of wind speed and wind energy resources in recent years.